Analisis Dan Perancangan Sistem Informasi Pemesanan Wedding Organizer Pada Organizer Organizer Mayang Decoration Jambi Berbasis Web - Sieskayadi, Prasetyo; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2020)
Organizer Organizer Mayang Decoration Jambi in promotion and order wedding organizer process stillget trouble, such as : reservation services need time and difficulty in order, sometimes get error inprocessing reservation wedding organizer data, and limited promotion package information. The purposeof research is analyzing and design information systems reservation wedding organizer in OrganizerOrganizer Mayang Decoration Jambi web-based using PHP programming language and MySQLdatabase. Metodology of this research use waterfall model and unified model language using use casediagram, activity diagram, and class diagram. Conclusion of this system can be made easier for customersto order package online and processing data to computerized. Research advice are prototyped this systemshould be devised well and properly so that it will could be applied to Organizer Organizer MayangDecoration Jambi